Unveiling the Hidden Enemies: Morphological and Molecular Characterization of Pod Rot Pathogens in Groundnut (Arachis hypogea L.) in India - , Sahana R, Viswanath K; Manjula, Nagamani P, Archana B. R; Kalpana (Archives of Current Research International, 2024)
Pod rot of groundnut is a complex disease caused by multiple pathogens causes significant economic losses. Present study was undertaken to know the pathogens associated with the disease. In Chittoor, Andhra Pradesh, roving survey against pod rot of groundnut revealed association of three fungal species: Sclerotium rolfsii, Rhizoctonia bataticola and Fusarium spp. Molecular analysis with modified CTAB method and performing PCR using ITS1 and ITS4 primers yielded DNA bands of 650-700 bp, 550-600 bp, and 500-600 bp for Sclerotium, Rhizoctonia and Fusarium species, respectively. Sequencing of the rDNA ITS region confirmed the identities of the pathogens as Sclerotium rolfsii, Rhizoctonia bataticola, Fusarium solani, Fusarium oxysporum, and Fusarium keratoplasticum, based on similarity with NCBI reference sequences. This study confirms that Sclerotium rolfsii, Rhizoctonia bataticola and Fusarium spp. are the primary causal agents of pod rot disease in Andhra Pradesh.